Natural and Derivatized Acetogenins Promising for the Control of Spodoptera frugiperda Smith - Ruiz Hidalgo, José (2016)
Annonaceous acetogenins (ACG), belonging to the family Annonaceae, represent aclass of bioactive compounds whose toxic effects have been reported for several species of insects. Given their insecticidal properties, we first carried out the isolation of the ACG from a Brazilian collection of the seeds of Annona squamosa (Annonaceae) and prepared their methoxy methylated (MOM) and acetylated (OAc) derivatives by chemical methods. ACG analogues were semi-synthesized and characterized by spectroscopic techniques (1H and 13C-NMR). We isolated ten natural acetogenins:squamocin, molvizarin, motrilin, rolliniastatin-2, almuñequin, cherimolin-1, cherimolin-2, annonacin, squamocin D and asiminecin. The main objective of this study is to report the antifeedant, toxic and nutritional effects of three of those natural acetogenins and their acetylated and methoxy methylated derivatives on Spodoptera frugiperda Smith (Lepidoptera: Noctuidae). The natural ACGs squamocin and molvizarin killed 100% of S. frugiperda larvae, followed by motrilin (80%). Acetylated derivatives had less toxic and nutritional effects that led to pupal mortality and adult fatal malformations. The addition of MOM derivatives to the larval diet has not toxic effects on larvae, but ignificantly reduces growth rate and efficiency in conversion of ingested food into biomass, affecting adult survival.